Prinsip Kepemimpinan Spiritual Pendidikan Islam Perspektif Al-Qu’ran - Sarkowi Sarkowi (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2020)
Abstract This article discusses the urgency of spiritual leadership in the world of education, which is examined from the perspective of the interpretation of the Koran. From the results of the study, it can be concluded that the character of spiritual leadership has three dimensions: being able to bring the worldly dimension to the spiritual dimension (divinity) and maintaining ethical values. Secondly, being able to motivate and inspire the civitas and stakeholders in Islamic educational institutions in achieving the vision and academic culture and morale of Islamic educational organizations. Third, able to create commitment and dedication of the entire community, which in turn also has an impact on increasing the sincerity and professionalism of serving the progress of Islamic educational institutions. Keywords; Leadership, Spiritual, Islamic Education, Al-Qur'an